Mobilité quotidienne en temps de crise - Lourdes Diaz Olvera; Didier Plat; Pascal Pochet (Belgeo)
During the last two decades, the growth of sub-Saharan African cities has taken place in a context of multiform crisis that affects the transport sector in several ways : scarce public resources, damaged roadway systems, disappearance of state-owned bus companies, proliferation of small informal transport enterprises, transport fares unaffordable for the household budget, etc. The analysis of the impact of the crisis on daily travel is based on data from surveys undertaken in seven cities. Access for poor populations to the city and to urban infrastructure and activities is hindered by deficiencies in transport supply and significant use of walking as a mode of transport. However, the crisis raises a strong contradiction in transport demand. While meeting daily travel needs is more complicated, increased daily travel is needed to find work in a context of high unemployment, to go shopping for very small quantities of products, in a more individualistic manner, and to maintain indispensable social networks. Thus, the crisis of the urban transport sector reflects and amplifies the economic crisis affecting African countries.